2021
DOI: 10.4055/cios20034
|View full text |Cite|
|
Sign up to set email alerts
|

Sensor-Assisted Total Knee Arthroplasty: A Narrative Review

Abstract: Wireless intraoperative load sensors have been used to improve the quality of soft-tissue balancing during total knee arthroplasty(TKA). Recent studies using the sensors have demonstrated reductions in gap imbalance, as well as early improvement of patient-reported clinical outcomes and low rates of arthrofibrosis. However, well-designed prospective studies are needed to determine whether the application of the sensor technology for TKA will have clinical benefits and improve the survival of prosthesis. Knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…First, it should be noted that the definition used to designate a balanced knee was proposed by Gustke et al in a non-evidence-based manner relying on previous biomechanical research on passive condylar pressures, intraoperative observations, and the observed significant drop-off in postoperative patient-reported outcome (PROM) scores with intercompartmental loading differences exceeding 20 lb. Despite so, to our knowledge, there are no validated target load in literature to designate a balanced knee, and this is the more commonly used [ 12 , 30 ]. Second, while the pressure values were obtained during surgery, as reported by Bellemans et al, there is evidence that stress relaxation of the ligaments occurs perioperatively and leads to increased ligament laxity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, it should be noted that the definition used to designate a balanced knee was proposed by Gustke et al in a non-evidence-based manner relying on previous biomechanical research on passive condylar pressures, intraoperative observations, and the observed significant drop-off in postoperative patient-reported outcome (PROM) scores with intercompartmental loading differences exceeding 20 lb. Despite so, to our knowledge, there are no validated target load in literature to designate a balanced knee, and this is the more commonly used [ 12 , 30 ]. Second, while the pressure values were obtained during surgery, as reported by Bellemans et al, there is evidence that stress relaxation of the ligaments occurs perioperatively and leads to increased ligament laxity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study attempted to identify the effect of rotation on measurements of alignment in the lower extremities. The results suggest that knee surgeons should be careful and opt for more sensitive investigations when diagnosing and planning treatment options in certain groups of patients [23,24]. The significance threshold for one-way analysis of variance (ANOVA) was set at P < 0:05.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in technology and surgical technique, recent evidence indicates that mechanically aligned (MA) total knee arthroplasty (TKA) does not improve residual symptoms, natural knee sensations, or patient satisfaction [ 1 , 2 , 3 , 4 , 5 ]. In addition, neutrally aligned TKA fails to reproduce patient-specific knee kinematics [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%